散装土榨花生油消费者KAP调查及信息干预效果评价KAP survey and evaluation of information intervention effect for consumers of bulk pressed peanut oil - 杨朝慧1,2， 何思蕾3， 邓俊锋3， 卢晓丹3， 何志妮3 YANG Zhaohui1,2, HE Silei3, DENG Junfeng3, LU Xiaodan3, HE Zhini3 (Zhongguo youzhi)
旨在为开展更具针对性的散装土榨花生油健康教育提供科学依据与支撑，基于对广西壮族自治区某村的问卷调研数据，通过KAP调查分析了消费者对散装土榨花生油质量安全知识认识、态度和行为意图，在此基础上通过微信交流群定期对受访者进行5次科普信息干预，并评价了干预的效果。结果表明：消费者对散装土榨花生油质量安全相关知识的知晓率(7.3%~42.5%)、正性态度率(3.1%~30.6%)、正性行为意图率（18.7%~52.3%）均较低；信息干预后，消费者对散装土榨花生油的质量安全相关知识知晓率(24.8%~67.6%)、正性态度率(3.4%~51.0%)和正性行为意图率(38.6%~60.0%)显著增加；不同年龄、受教育程度、月平均收入、身体健康状况人群对散装土榨花生油的认知、态度、行为均存在明显差异。综上，应根据不同人群的特点和需求，有针对性地开展科普活动，积极引导消费者掌握必要的食品科学知识，养成更加健康的饮食习惯和生活方式。 To provide scientific evidence and support for implementing targeted health education programs regarding bulk pressed peanut oil, based on questionnaire survey data from a village in the Guangxi Zhuang Autonomous Region, consumers′ knowledge, attitudes, and behavioral intentions towards the quality and safety of bulk pressed peanut oil were analyzed through the KAP survey. Subsequently, five rounds of science popularization information intervention through Wechat communication groups were conducted and their effectiveness were evaluated. The results showed that consumers initially exhibited low awareness (7.3%-42.5%), positive attitude rates (3.1%-30.6%), and positive behavioral intention rates (18.7%-52.3%). Post-information intervention, these metrics significantly increased to 24.8%-67.6%, 3.4%-51.0%, and 38.6%-60.0%, respectively. Notable differences were observed in the knowledge, attitudes and practice of people across age groups, education levels, incomes, and health statuses toward bulk pressed peanut oil. In conclusion, tailored communication strategies should be developed based on population-specific characteristics and needs, to guide consumers in acquiring food safety knowledge and adopting healthier lifestyles.